LEVEL OF PRE-TERTIARY CARE HOSPITAL MANAGEMENT OF TRAUMATIC SPINAL CORD INJURED PATIENTS; WHERE DO WE STAND? - Shahbaz Ali Khan,; Khalid, Shah; Abdul Aziz Khan,; Zanib Javed,; Jawwad Hussain,; Ehtisham Ahmed Khan Afridi,; Muhammad Zeeshan Haroon,; Ahsan Aurangzeb, (Journal of Ayub Medical College Abbottabad, 2021)
Background: Traumatic spinal cord injury is a debilitating condition that may cause long term disabilities with tremendous socioeconomic impact on affected individuals and their families. Secondary injuries can best prevent or minimized by appropriate pre hospital management and proper referral and transfer. This study was conducted to assess the clinical profile of traumatic spinal cord injuries and level of pre-hospital care provided to patients either at the site of injury or at other healthcare facilities. Methods: This prospective study was conducted in the Department of Neurosurgery Ayub Teaching Hospital Abbottabad, from January 2012 to January 2017. All patients with suspected spinal injury were included in the study. Age, gender, mode of injuries and the pre-tertiary care provided were recorded. Results: Out of 4464 patients with suspected spinal cord injury, 3685 (82.5%) were male, 779 (17.4%) were female. Age ranged from 10-70 years. 1685 (37.8%) were diagnosed as having spinal injury. Cervical spine was the most common affected level 743 (44.09%), followed by thoracic spine 135 (8.01%). 1441 (85.5%) were incomplete while 224(14.5%) were complete spinal cord injuries. Road traffic accident was the most common mechanism of injury 884 (52.4%). Only 4 (0.23%) patients directly received in our unit were properly transported, 66 (3.91%) were brought after proper spinal immobilization, intravenous line was maintained in 584 (34.66%) patients, 410 (24.3%) patients received some fluid resuscitation, parenteral analgesia was given to 441 (26.17%) patients while urinary catheterization was done in 195 (11.75%) patients. Those received from other healthcare facilities only 4 (0.23%) were brought by properly equipped ambulance, intravenous access was maintained in 438 (25.99%),320 (18.99%) received some fluid resuscitation, urinary catheterization was done in 229(13.59%) while proper parenteral analgesia was given to 988 (58.63%) patients. Conclusion: There is a complete lack of proper transport and referral of trauma patients in our area which reflects almost non-existent emergency medical (rescue) services, deficient health care facilities.